Overview of the detection and tracking methods of the lab animals - Maksym Shvandt; Volodymyr Moroz (Sistemnì Doslìdženâ ta Informacìjnì Tehnologìï, 2022)
This article presents an overview of several most common techniques and approaches for object detection and tracking. Today, the tracking task is a very common problem and it can appear in many aspects of our life. One particular case of using object tracking techniques can appear during a lab animal behavior study. Different experimental conditions and the need of certain data collection can require some special tracking techniques. Thus, a set of general approaches to object tracking techniques were considered, and their functionality and possibilities were tested in a real life experiment. In this paper, their basis and main aspects are presented. The experiment has demonstrated the advantages and disadvantages of the studied methods. Considering this, conclusions and recommendations to their usage cases were made.